Poetic form in Blake's Milton - Fox, Susan, 1943- (Princeton, New Jersey : Princeton University Press, 1976)
Blake's two finished epics have been widely regarded as combinations of brilliant set pieces which yield to no systematic rhetorical criticism. Susan Fox contests this view, discovering in Milton an elaborate verbal structure that is fully congruent with the poem's philosophy. She has made the first full exposition of the formal principles of a late Blake poem, and it suggests that the late prophecies are as profound in their artistic structures as they are in their thematic ones. The author begins by tracing throughout Blake's poetry the development of the techniques found in Milton. She then provides an analysis in two chapters organized, as she perceives the poem to be, in parallel three-part units. Her examination reveals the exhaustive parallelism of the poem's books, as well as more local devices such as paired stanzas and circular rhetoric. The rhetorical pattern which emerges raises several major thematic issues which are treated in the concluding chapter. In demonstrating the coherence and control of the intricate formal patterns of Milton, this study provides a new measure of Blake's late verbal art.Originally published in 1976.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- List of Illustrations -- Preface -- Acknowledgments -- I. Contexts -- II. Hammer -- III. Loom -- IV. Contraries and Progression -- APPENDIX A : Illuminations and Structure -- APPENDIX B: Revisions and Structure -- Index
Includes index.
Print version record.
eBooks on EBSCOhost
Keywords: Blake, William, -- 1757-1827.; Milton, John, -- 1608-1674 -- In literature; Milton, John, -- 1608-1674 -- In literature; Blake, William, -- 1757-1827.; Milton, John, -- 1608-1674; Milton (Blake, William); POETRY -- Epic; POETRY -- English, Irish, Scottish, Welsh; Literature